Association between BAX promoter variant and papillary thyroid carcinoma in a group of Egyptian patients - Aisha O. Tolba; Amaal A. Abdelaal; Noha Osama Mohamed Ragaey; Ahmad Mohamed Eltelety; Amal Bahgat Fakhry (The Egyptian Journal of Otolaryngology)
Abstract Background Pro-apoptotic BAX protein plays a crucial role in mitochondrial-dependent apoptosis regulation. Single nucleotide variants (SNVs) in the BAX gene may serve as genetic risk markers for predicting the occurrence of cancer susceptibility and defining high-risk individuals. The aim of this study was to investigate the association of the BAX rs4645878 variant with papillary thyroid carcinoma (PTC) risk in a group of Egyptian patients. Methods The study was conducted on 50 PTC patients, 50 patients with non-malignant thyroid disease and 50 healthy individuals as controls. The genotyping of the BAX rs4645878 variant was carried out using the TaqMan Real-Time Polymerase Chain Reaction (PCR) assay. Results The BAX rs4645878 variant analysis showed no statistically significant difference in the frequency of genotypes and alleles between all studied groups (P > 0.05). There was a statistically significant difference in neck ultrasound TIRADS score between the PTC and non-malignant thyroid disease groups (P < 0.001). However, we found a non-significant association between TIRADS score and BAX rs4645878 variant (P > 0.05). The study revealed a significant association between genotypes of the BAX rs4645878 variant and PTC risk in female patients (P = 0.044), but not in males (P > 0.05). Compared with the combined genotypes (A/G + A/A), the G/G genotype was associated with an elevated risk of PTC among females (OR = 6.2, 95% CI = 1.2–31.3). Similarly, the G allele was associated with 6.9 times more risk of having PTC in females compared with the A allele (OR = 6.9, 95% CI = 1.5–32.3, P = 0.022). Conclusion The G/G genotype and G allele of the BAX rs4645878 variant can serve as genetic risk markers for PTC susceptibility among females.